Nutrition and Central Nervous System - Mohajeri, M. Hasan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The focus of this Special Issue is "Nutrition and the Central Nervous System". The brain is, as a very specialized and one of the most metabolically active organs of the body, dependent on a steady and sufficient supply of dietary ingredients. The critical role of the diet for brain development as well as for proper CNS functioning and the possible preventative roles against neurodegenerative and neurological conditions is commonly accepted. The overarching aim of this Special Issue is pinpointing the mechanisms of action and publishing state-of-the-art contributions discussing the roles that nutritional compounds play in the development, maintenance, and aging of the CNS.